MONITORING EMISI KENDARAAN BERMOTOR KARBON DIOKSIDA (CO_2), KARBON MONOKSIDA (CO) BERBASIS ARDUINO DAN ESP8266 - Zakaria, Risman; Priyandoko , Gigih; Setiawidayat, Sabar (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2024)
Motorized vehicles are currently circulating a lot on the streets. Every motor vehicle produces what is called exhaust gas or what we often call motor vehicle emissions. By monitoring the exhaust gases produced by the vehicle, it means that the vehicle owner is much more concerned about the pollutants that can be produced by the vehicle itself, so that the vehicle owner can minimize the pollutants produced by the vehicle. This tool for monitoring the emission of wifi-based motor vehicles uses several components including Arduino uno, nodemcu esp8266, mq2 sensor, mq7 sensor with applications as program support, namely Arduino Ide, Firebase. The testing of this motor vehicle emission monitoring device is carried out by placing the mq2 and mq7 sensors right in front of the exhaust as the place where the vehicle's emissions come out. The comparison of the vehicle test results was carried out to see how much carbon monoxide and carbon dioxide levels were produced in each vehicle after being tested using the tool where the average carbon monoxide content for avansa vehicles was 13.56 ppm, ignis vehicles was 12.84 ppm, and innova vehicles were 175.02 ppm. While the recommended carbon monoxide level < 25 ppm, vehicles that have carbon monoxide levels above (Threshold Value) do not pass the emission test. And for the average carbon dioxide level testing in avanza vehicles of 385.7 ppm, ignis vehicles of 302.6 ppm, innova vehicles of 956.4 ppm. While the recommended carbon dioxide level < 450 ppm, vehicles that have a carbon dioxide content value above (Threshold Value) do not pass the emission test. Keywords : Motor vehicle emissions, MQ2 and MQ7 sensors as CO2 and CO detectors for monitoring.